Applying the classic rape scenario to robbery: An examination of situational characteristics and reporting victimization to police. (January 2021) - Muniz, Caitlyn N.; Powers, Ráchael A.
Abstract: The classic rape scenario creates an expectation that "real rape" only occurs in the context of certain situational characteristics. These stereotyped expectations are attributed to the low rates of sexual assault reporting especially when compared to other violent crimes like robbery. However, the literature on sexual assault reporting has been divorced from the larger criminological literature on reporting with few comparisons to other types of crimes, therefore the uniqueness of these situational factors for sexual assault is unknown. Robbery is particularly well-suited for comparison to sexual assault due to the presence of situational characteristics similar to those of "real rape" and a lack of stereotyped expectations of victimization. Using logistic regression and multiequation probit modeling, this study employs the NCVS to explore the decision to report robberies and sexual assaults to police and the differences attributed to negative perceptions of police for nonreporters. We found that robberies were indeed more likely to reflect the classic scenario and thus more accurately reflect what is expected in the classic rape scenario. However, few differences were found in regards to the decision to report and reasons for nonreporting across classic scenario characteristics. Implications and directions for future research are discussed. Highlights: The classic rape scenario more accurately describes robbery than sexual assault. Sexual assault incidents are less likely to be reported than robbery, even when controlling for situational factors. Perceptions of police bias influenced nonreporting for sexual assault incidents. There are underlying racial issues related to reporting to police that particularly influence victims of sexual violence.